2023
DOI: 10.1007/s40812-022-00247-9
|View full text |Cite
|
Sign up to set email alerts
|

The virtues and limits of specialization in global value chains: analysis and policy implications

Abstract: A growing concern has emerged in both academic research and policy circles about the hidden risks that can arise from a narrow specialization of economies in a world characterized by the international fragmentation of production. In this work, we address the virtues and limits of specialization in light of the strong interdependencies between countries induced by the emergence and evolution of global value chains (GVCs). The need to shift the focus from the product level to the functional level is discussed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…Third, we found that a greater functional diversification in FDI is robustly associated with lower levels of income disparities within countries. This result appears consistent with the hypothesis that a larger mix of value-adding activities an economy carries out allows to expand the learning opportunities and occupational choices for its workers and is conducive to a more inclusive development (Coveri & Zanfei, 2023) (Windmeijer, 2005). All explanatory variables, except the years of compulsory education and the KOF financial globalization index (de facto), are treated as endogenous.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Third, we found that a greater functional diversification in FDI is robustly associated with lower levels of income disparities within countries. This result appears consistent with the hypothesis that a larger mix of value-adding activities an economy carries out allows to expand the learning opportunities and occupational choices for its workers and is conducive to a more inclusive development (Coveri & Zanfei, 2023) (Windmeijer, 2005). All explanatory variables, except the years of compulsory education and the KOF financial globalization index (de facto), are treated as endogenous.…”
Section: Discussionsupporting
confidence: 80%
“…However, the "slicing up" of GVCs has prompted a hyper-specialization of world economies in selected value chain functions of the GVCs of products, be they a Barbie doll or an iPhone (Tempest, 1996;Kaplan and Kaplinsky, 1999;Dedrick et al, 2010;Grossman & Rossi-Hansberg, 2008;Timmer et al, 2019). It follows that greater attention should be paid to the diversification of economies in terms of GVC functions rather than products (Sturgeon, 2008;Sturgeon & Gereffi, 2009;Coveri & Zanfei, 2023).…”
Section: Literature Review and Research Questions 21 Global Value Cha...mentioning
confidence: 99%
See 1 more Smart Citation
“…We note a recent study which positions the efficiency-resilience trade-off at the national, rather than the firm level (Coveri & Zanfei, 2023). It argues that comparative advantage and functional specialization create vulnerability.…”
Section: Myth 2: Efficient Supply Chains Are Less Resilientmentioning
confidence: 84%
“…A narrative has emerged (Evenett, 2022) that implies that deglobalization is inevitable because international supply chains are inadequately resilient and trade partners hostile (Foroohar, 2022;Coveri & Zanfei, 2023;Witt et al, 2023). Terms like 'friend-shoring' have been introduced into the policy discourse, with some voices insisting that the virtues of regional supply chains exceed those of the global ones (O'Neil, 2022).…”
mentioning
confidence: 99%